Frontiers: How Support for Black Lives Matter Impacts Consumer Responses on Social Media - Wang, Yang; Qin, Marco Shaojun; Luo, Xueming; Kou, Yu (Eric) (Marketing Science, 2022)
This paper studies the direct and moderated impact of brands’ support for Black Lives Matter (BLM) on consumer responses.